2019
DOI: 10.1111/bju.14704
|View full text |Cite
|
Sign up to set email alerts
|

The impact of non‐urothelial variant histology on oncological outcomes following radical cystectomy

Abstract: ConclusionOur results showed a risk of shorter survival in NUVH compared to PUC. This suggests NUVH as an independent predictor of worse outcomes. As a result, patients with NUVH should be counselled preoperatively that overall and disease-specific outcomes are worse postoperatively and about the possible need for adjuvant treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 14 publications
1
10
1
Order By: Relevance
“…We report that 43% of patients had VH, with SQD (16%), mixed VH (9.9%) and MPV (5.5%) being the most common variants. Although the frequency of VH reported in our cohort is superior of those reported in largest series published in the past few years, which have found prevalences of VH between 17-32%, VH subtypes proportions is in concordance, being SQD and MPV between the most common variants reported (8)(9)(10)(11).…”
Section: Resultscontrasting
confidence: 83%
“…We report that 43% of patients had VH, with SQD (16%), mixed VH (9.9%) and MPV (5.5%) being the most common variants. Although the frequency of VH reported in our cohort is superior of those reported in largest series published in the past few years, which have found prevalences of VH between 17-32%, VH subtypes proportions is in concordance, being SQD and MPV between the most common variants reported (8)(9)(10)(11).…”
Section: Resultscontrasting
confidence: 83%
“…These different histologic subtypes have been suggested to differ in terms of risk factors, prognostic indicators, clinical outcomes, response to treatment modalities, and even incidence. [5][6][7][8][9][10][11][12][13][14] One study, using the SEER United States population dataset, showed a decreased incidence of SCC of the bladder from 1973 to 2013. 5 However, the clinical significance of squamous differentiation and pure SCC of the bladder continues to be debated.…”
Section: Introductionmentioning
confidence: 99%
“…Stroman et al reported a decrease in overall survival in patients with histological variants at 14% at 2 years and 23% at 5 years after RC compared to pure UC. Patients should be informed about the high risk and unpredictable nature of these entities and the recommendation for the first RC performed for this indication [17].…”
Section: Discussionmentioning
confidence: 99%